Tailoring ionic-electronic transport in PEO-Li4C60: Towards a new class of all solid-state mixed conductors. (April 2016) - Cattaneo, A.S.; Dall'Asta, V.; Pontiroli, D.; Riccò, M.; Magnani, G.; Milanese, C.; Tealdi, C.; Quartarone, E.; Mustarelli, P.
Abstract: Mixed ionic-electronic conductors (MIEC) are of growing interest for fuel cells, batteries and sensors. Here, by exploiting the unique properties of Li4 C60 2D fulleride and poly(ethylene oxide) (PEO), we demonstrate the feasibility of a MIEC where the nature of transport can be tuned from ionic, to mixed, to almost entirely electronic, simply by changing the weight ratio of the two basic components. By coupling 7 Li MAS-NMR, electrochemical impedance spectroscopy and open circuit voltage (OCV) measurements of a Li/composite/LiFePO4 cell we demonstrate that: i) a fraction of Li + ions is extracted by Li4 C60 and confined into PEO amorphous strands similarly to what happens in PEO-salt systems; ii) a transition between prevalently ionic and electronic conductivity takes place at 33 wt% Li4 C60 . This new class of MIEC is very promising for the design of both chemically and electrochemically stable semi-cells and interfaces which can be employed in batteries and supercapacitors.